Sustainable Economic Empowerment Through Collaborative Village Governance and Social Entrepreneurship Education Toward Achieving A Circular Economy - Ikhsan Nendi (Inkubis : Jurnal Ekonomi dan Bisnis, 2025)
Background: This study examines village collaborative governance models and community-based social entrepreneurship education in realizing a sustainable rural circular economy. Objective: The main focus of the research is to identify and analyze governance models that can support sustainable economic empowerment, as well as to assess the effectiveness of community-based social entrepreneurship education in enhancing the entrepreneurial capacity of rural communities through circular economy principles. Method: The research employs a mixed-methods approach (qualitative and quantitative), with data analysis including in-depth interviews, participatory observation, and quantitative surveys. Findings and Implications: The main findings indicate that the implementation of collaborative governance models involving various stakeholders, along with community-based social entrepreneurship education based on circular economy principles, can enhance economic resilience and create sustainable business opportunities. Conclusion: The implications of this research emphasize the importance of integrating the development of village governance capacity with entrepreneurship education to create independent and environmentally-friendly rural economies. This study also provides recommendations for policies that foster rural economic development through community-based empowerment models grounded in circular economy governance.